2018
DOI: 10.1101/357152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endometrial receptivity revisited: endometrial transcriptome adjusted for tissue cellular heterogeneity

Abstract: (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.Thecopyright holder for this preprint . http://dx.doi.org/10.1101/357152 doi: bioRxiv preprint first posted online Jun. 28, 2018; 3 PARTICIPANTS/MATERIAL, SETTING, METHODS Paired early-and mid-secretory 50endometrial biopsies were obtained from thirty-five healthy, regularly cycling, fertile volun-51 teers, aged 23 to 36 years, and analysed by RNA sequencing. Differential gene expression … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Sequencing data analysis was performed as described previously [3], and each sample was normalized using geometric mean of gene expression levels of four housekeeper genes. The same sequencing protocol was applied to 54 paired endometrial samples from 27 healthy parous women, collected at the histologically and biochemically [predicted from the luteinizing hormone (LH) peak in urine] confirmed ES and MS cycle phases (described in [5]). The resulting data were used to create a machine learning support vector machine (SVM) model for discrimination of ES and MS phase samples.…”
mentioning
confidence: 99%
“…Sequencing data analysis was performed as described previously [3], and each sample was normalized using geometric mean of gene expression levels of four housekeeper genes. The same sequencing protocol was applied to 54 paired endometrial samples from 27 healthy parous women, collected at the histologically and biochemically [predicted from the luteinizing hormone (LH) peak in urine] confirmed ES and MS cycle phases (described in [5]). The resulting data were used to create a machine learning support vector machine (SVM) model for discrimination of ES and MS phase samples.…”
mentioning
confidence: 99%
“…The difference in expression patterns between study groups was not statistically significant in the present study which might be due to whole-tissue samples used for analysis. Suhorutshenko et al [ 66 ] demonstrated that expression contribution of low abundant cell types in heterogeneous tissue could be masked by more abundant types. They compared paired endometrium biopsy samples collected in pre-receptive (early-secretory, ES) and receptive (mid-secretory, MS) states and estimated that ES samples consisted of 65% stromal and 35% epithelial cells, while the proportion of stromal and epithelial cells in MS samples was 46% and 54%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Human endometrium has been investigated extensively for its global molecular repertoire and modulation in response to hormones, drugs, and diseases. Majority of these investigations have focused on the transcriptome of whole tissue (Altmae et al, ; Borthwick et al, ; Carson et al, ; Haouzi et al, ; Horcajadas et al, ; Hu et al, ; Mirkin et al, ; Riesewijk et al, ; Suhorutshenko et al, ; Talbi et al, ). Strides have also been made to develop the endometrial proteome (Chen et al, ; DeSouza et al, ; Dominguez et al, ; Hood et al, ; Parmar et al, ; Rai, Kota, Sundaram, Deendayal, & Shivaji, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctions in any of these cell types can lead to impaired endometrial functions and infertility. This has triggered efforts to develop endometrial cell‐type‐specific transcriptome or proteome (Evans et al, ; Suhorutshenko et al, ). However, data on the plasma membrane proteome of endometrial epithelial cells are scarce.…”
Section: Discussionmentioning
confidence: 99%